Neuropalliative Care: A Practical Guide for the Neurologist - Brizzi, K.; Creutzfeldt, C. J. (Seminars in Neurology, 2018)
Neuropalliative care is a new and growing field within neurology that focuses on improving the quality of life of patients with serious neurologic illnesses. While specialty-level palliative care training is available to interested neurologists, all neurologists can strive to provide primary palliative care for their patients. In this review, we will describe the scope of neuropalliative care, define patient populations who may benefit from palliative care, and explore the communication and symptom management skills essential to palliative care delivery.
Keywords: palliative care; neuropalliative care; quality of life; communication skills